1988
DOI: 10.1093/ije/17.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Factors in Multiple Sclerosis: A Review and Critique of the Epidemiological Literature

Abstract: A review of the international epidemiological literature is undertaken with the view of identifying the main demographic and sociocultural features of MS as they apply to ethnic groups. Ethnic groups are differentiated principally in terms of three variables: race, religion, and nationality. Although MS is present in the three principal racial groups in the world (white, oriental, and black), it tends to be unequally distributed. Four hypotheses are formulated regarding the unequal susceptibility of the races … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…These results were as ex pected for a community in Ohio. As has been observed in other studies [4,5], cases tended to have higher titers to measles virus and to the chickenpox virus than controls.…”
Section: Discussionsupporting
confidence: 86%
“…These results were as ex pected for a community in Ohio. As has been observed in other studies [4,5], cases tended to have higher titers to measles virus and to the chickenpox virus than controls.…”
Section: Discussionsupporting
confidence: 86%
“…For example, the American official rate, given by health autho rities is 67.7 per 105 inhabitants; if we calcu late the theoretical MS prevalence rate with our formula, we find: y = 66. 22.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors agree with the fact that dif ferent cofactors play a role in MS: genetic fac tors including major histocompatibility com plex genes [19][20][21], ethnic [22], environmen tal, geographical [23][24][25], traumatic [26] and dietary factors. The latter include meat pres ervation techniques [27], fatty acid consump tion [28][29][30], and heavy metals in drinking water [31].…”
Section: Introductionmentioning
confidence: 99%
“…The strong negative correlation for North American natives found in this study supports a genetic contribution based on parental ancestry. Interestingly, Lowis [14] has suggested that ethnie heterogene ity may be a risk factor for MS, noting low MS rates among Spanish-speaking groups in the US and Mexico and commenting that this group tends to be particularly homogeneous both in terms of genetics and life-style. The lowest single ancestry group in our study was female MS patients.…”
Section: Discussionmentioning
confidence: 99%